Sistem Pemesanan Online Lapangan Futsal Berbasis Web pada PK Futsal - Aditya Dharmawan; Mira Ziveria (UNIVERSITAS KALBIS, 2022)
PK Futsal is an organization that provides futsal field rental services. PK Futsal's system for field ordering is still based on the conventional method. This research intends to develop a web-based online ordering information system using Prototyping system development methods, Unified Modeling Language (UML) system modeling, Hypertext Preprocessor (PHP) system programming, and Black Box Testing to test the system. This study produced a system that can be used to view the availability of field schedules and book fields online at PK Futsal.